Histopathological Spectrum of Ovarian Neoplasms and their Clinicopathological Correlation - Arpitha K; Anuradha G Patil; Anita A.M.; Shivanand S Devarmani; Rajshekar S Jewargikar; Asha Patil (International Journal of Health and Clinical Research, 2021)
Introduction: Ovary is a small organ and unique in terms of variety of lesions that arise from it[1]. Worldwide, ovarian cancer is sixth most common cancer in women and most frequent cause of death from gynecologiccancer[1]. Even though immunohistochemical and chromosomal studies have made diagnosis and differentiation of tumours easier, in developing countries like India, cost effective histomorphological studies still form the backbone of diagnosis of these tumours[2].Materials and Methods: All the slides of cases in the retrospective period were reviewed. All the specimens were processed after detailed gross examination, extensive sampling was done. The processed tissue was paraffin embedded and sections were cut at 4-5μ thickness and stained with Haematoxylin and Eosin stain and thoroughly examined. Special stains were done wherever necessary. The tumors were diagnosed and classified according to World health organization histopathological classification of ovarian tumors. Results: Microscopic analysis showed 82 cases of surface epithelial tumors among them 78 are benign consisting of 56 Serous cystadenomas , 19 Mucinous cystadenomas , 01 case of serous cystadenofibroma, 02 cases of Brenner tumor and 04 Serous cystadeno-carcinomas. There were 15 cases of Teratoma , 02 cases of Dysgerminoma and Mixed germ cell tumor. There were 01 case of each Fibroma , Thecoma and Fibrothecoma, 02 case of Granulosa cell tumor. There were 01 case each of Hemangioma and Lymphangioma. Secondaries were Adenocarcinomas from Stomach and Cervix .Conclusion: Ovarian tumours are one of the most researched topics in gynaecological pathology. During the present study , it was found that the incidence of ovarian neoplasms was almost the same in this region when compared with the previous data.